A Method to Study α-Synuclein Toxicity and Aggregation Using a Humanized Yeast Model - Kim, Hyunhee; Jeong, Juwon; Lee, Changhan (Journal of Visualized Experiments, 2022)
Parkinson's disease is the second most common neurodegenerative disorder and is characterized by progressive cell death caused by the formation of Lewy bodies containing misfolded and aggregated α-synuclein. α-synuclein is an abundant presynaptic protein that regulates synaptic vesicle trafficking, but the accumulation of its proteinaceous inclusions results in neurotoxicity. Recent studies have revealed that various genetic factors, including bacterial chaperones, could reduce the formation of α-synuclein aggregates in vitro. However, it is also important to monitor the anti-aggregation effect in the cell to apply this as a potential treatment for the patients. It would be ideal to use neuronal cells, but these cells are difficult to handle and take a long time to exhibit the anti-aggregation phenotype. Therefore, a quick and effective in vivo tool is required for the further evaluation of in vivo anti-aggregation activity. The method described here was used to monitor and analyze the anti-aggregation phenotype in the humanized yeast Saccharomyces cerevisiae, which expressed human α-synuclein. This protocol demonstrates in vivo tools that could be used for monitoring α-synuclein-induced cellular toxicity, as well as the formation of α-synuclein aggregates in cells.
Keywords: alpha-Synuclein; Humans; Inclusion Bodies; Parkinson Disease; Saccharomyces cerevisiae; Synaptic Vesicles